Pengaruh Minat Belajar Terhadap Kesulitan Belajar Mahasiswa Pada Mata Kuliah Pengantar Akuntansi Prodi Pendidikan Administrasi Perkantoran - Nadiya Rahmadina; Marsofiyati Marsofiyati (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
In the learning process, many students experience learning difficulties. The problem of learning difficulties often faced by students needs to be understood as something important to get serious attention by educators. It is important for students to foster interest in learning. Interest in learning is important for individuals in achieving their goals. Interest in learning can increase learning awareness, focus, and self-confidence. The purpose of this study was to determine the relationship between learning interest and learning difficulties in the introductory accounting course of Office Administration Education Study Program students. The sample in this study were some students of the Office Administration Education Study Program class of 2022 as many as 30 students. This study uses quantitative methods and questionnaire instruments with data analysis methods using the coefficient of determination test and multiple linear regression tests. The results of this study indicate that there is no effect of learning interest on student learning difficulties in introductory accounting courses. After calculating using SPSS, it was found that Fhitung = 0.213 ≤ Ftabel = 4.20. From the research, it was found that the learning interest variable had an effect of 0.8% on changes in the dependent variable, namely learning difficulties. While the remaining 99% is influenced by other variables.